2021
DOI: 10.3390/jmse9111222
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extreme Storm Surges over the Changjiang River Estuary from a Wave-Current Coupled Model

Abstract: Disastrous storm surges and waves caused by typhoons are major marine dynamic disasters affecting the east China coast and the Changjiang River Estuary, especially when they occur coincidentally. In this study, a high-resolution wave–current coupled model consisting of ADCIRC (Advanced Circulation) and SWAN (Simulating Waves Nearshore) was established and validated. The model shows reasonable skills in reproducing the surge levels and waves. The storm surges and associated waves are then simulated for 98 typho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Other human reconstructions, such as the Deep Waterway Project, with the purpose of deepening the navigation channel, have also been implemented [6]. Meanwhile, the CRE experiences severe typhoon storms almost every year, leading to coastal hazards such as catastrophic waves and storm surges [7][8][9]. In addition to typhoons in the summer, severe wave disasters have also been observed frequently over the CRE during cold weather events in winter.…”
Section: Introductionmentioning
confidence: 99%
“…Other human reconstructions, such as the Deep Waterway Project, with the purpose of deepening the navigation channel, have also been implemented [6]. Meanwhile, the CRE experiences severe typhoon storms almost every year, leading to coastal hazards such as catastrophic waves and storm surges [7][8][9]. In addition to typhoons in the summer, severe wave disasters have also been observed frequently over the CRE during cold weather events in winter.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 30 years, many typhoons have struck this coastal area, causing severe coastal flooding, infrastructure damage and huge economic losses [4]. For example, the super typhoon Chan-hom in 2015 caused economic losses of over RMB 9.8 billion [5]. However, due to the complex coastline and topography, as well as the many offshore islands, it is complex and difficult to accurately predict the storm surge and waves in the Changjiang River Estuary and adjacent seas.…”
Section: Introductionmentioning
confidence: 99%
“…Wave prediction is of crucial importance to human activities as it provides useful information for many coastal engineering applications such as the coastal protection, environmental monitoring, navigation, safe port management, and good control of recreational activities in popular coastal areas [14]. Both observational and measurement data, as well as physical and numerical models, are often used to assess extreme marine events around the world [15]. Chi and Rong [15] confirmed that long-term in situ observations can accurately estimate the sea level variation but are usually spatially limited.…”
Section: Introductionmentioning
confidence: 99%
“…Both observational and measurement data, as well as physical and numerical models, are often used to assess extreme marine events around the world [15]. Chi and Rong [15] confirmed that long-term in situ observations can accurately estimate the sea level variation but are usually spatially limited. The authors also indicated that many numerical models have been developed and validated to reproduce the spatial and temporal variation of wave spreading and uncover the underlying dynamics.…”
Section: Introductionmentioning
confidence: 99%